Simultaneous improvement of the thermostability and activity of lactic dehydrogenase from Lactobacillus rossiae through rational design. Issue 51 (21st November 2022) - Luo, Xi; Wang, Yifeng; Zheng, Weilong; Sun, Xiaolong; Hu, Gaowei; Yin, Longfei; Zhang, Yingying; Yin, Fengwei; Fu, Yongqian
Abstract : The d -LDH was engineered using computationally-assisted rational mutagenesis. The two mutants D249A and D249A/T247I showed significantly enhanced thermostability and catalytic activity to sodium phenylpyruvate compared with the wild-type enzyme. Abstract : d -Phenyllactic acid, is a versatile organic acid with wide application prospects in the food, pharmaceutical and material industries. Wild-type lactate dehydrogenase Lr LDH from Lactobacillus rossiae exhibits a high catalytic performance in the production of d -phenyllactic acid from phenylpyruvic acid or sodium phenylpyruvate, but its industrial application is hampered by poor thermostability. Here, computer aided rational design was applied to improve the thermostability of Lr LDH. By using HotSpot Wizard 3.0, five hotspot residues (N218, L237, T247, D249 and S301) were identified, after which site-saturation mutagenesis and combined mutagenesis were performed. The double mutant D249A/T247I was screen out as the best variant, with optimum temperature, t 1/2, and T 1050 that were 12 °C, 17.96 min and 19 °C higher than that of wild-type Lr LDH, respectively. At the same time, the k cat / K m of D249A/T247I was 1.47 s −1 mM −1, which was 3.4 times higher than that of the wild-type enzyme. Thus rational design was successfully applied to simultaneously improve the thermostability and catalytic activity of Lr LDH to a significant extent. The results of molecular dynamics simulations and molecular structure analysis could explain the mechanisms for the improved performance of the double mutant. This study shows that computer-aided rational design can greatly improve the thermostability of d -lactate dehydrogenase, offering a reference for the modification of other enzymes.